2021
DOI: 10.3389/fvets.2021.727766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Diquat Poisoning on Liver Mitochondrial Apoptosis and Autophagy in Ducks

Abstract: Diquat (DQ) is an effective herbicide and is widely used in agriculture. Due to persistent and frequent applications, it can enter into aquatic ecosystem and induce toxic effects to exposed aquatic animals. The residues of DQ via food chain accumulate in different tissues of exposed animals including humans and cause adverse toxic effects. Therefore, it is crucial and important to understand the mechanisms of toxic effects of DQ in exposed animals. We used ducks as test specimens to know the effects of acute D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…In this paper, excessive V upregulated the mRNA and protein levels of Drp1 and MFF in the heart of ducks, and downregulated the mRNA and protein levels of OPA1, Mfn1, and Mfn2, which indicated that V promoted mitochondrial fission in the heart of ducks but inhibited mitochondrial fusion. In addition, there are mainly PINK1/Parkin, Bnip3/Nix, and FUNDC1 pathways to regulate mitophagy, and PINK1/Parkin pathway is closely related to the regulation of mitochondrial function ( 51 , 52 ). In this pathway, PINK1 selectively acts on the upstream of Parkin when mitochondria depolarize and accumulate on the damaged mitochondria to activate Parkin's translocation to the mitochondria, which then triggers mitophagy ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, excessive V upregulated the mRNA and protein levels of Drp1 and MFF in the heart of ducks, and downregulated the mRNA and protein levels of OPA1, Mfn1, and Mfn2, which indicated that V promoted mitochondrial fission in the heart of ducks but inhibited mitochondrial fusion. In addition, there are mainly PINK1/Parkin, Bnip3/Nix, and FUNDC1 pathways to regulate mitophagy, and PINK1/Parkin pathway is closely related to the regulation of mitochondrial function ( 51 , 52 ). In this pathway, PINK1 selectively acts on the upstream of Parkin when mitochondria depolarize and accumulate on the damaged mitochondria to activate Parkin's translocation to the mitochondria, which then triggers mitophagy ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diquat has been reported to be toxic to humans and animals and the damage caused by its toxic effects can be roughly classified into the following two types: 1 , 25 , 26 First, diquat produces direct contact burns in humans and animals, resulting in tissue necrosis, mucosal erosion, or hemorrhage. 1 , 26 , 27 Secondly, it also activates a reduction-oxidative process that generates ROS and RNS in cells, leading to oxidative stress, which in turn leads to cellular dysfunction. 1 , 26 It was previously found that diquat-induced superoxide damages mitochondria and endoplasmic reticulum, initiates autophagy, and induces apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 26 , 27 Secondly, it also activates a reduction-oxidative process that generates ROS and RNS in cells, leading to oxidative stress, which in turn leads to cellular dysfunction. 1 , 26 It was previously found that diquat-induced superoxide damages mitochondria and endoplasmic reticulum, initiates autophagy, and induces apoptosis. 13 , 28 In this study, we found that diquat reduced the viability of HK-2 cells, and that apoptosis is triggered by HK-2 cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in the United States, between 1998 and 2013, 300 acute illnesses were associated with paraquat, while 144 were linked to DQ exposure, with herbicide spillage or splashing being a signi cant cause of such illnesses [17]. Furthermore, DQ exposure has been shown to damage multiple organs, including the kidneys, lungs, small intestines, liver, and central nervous system [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%